Self-reflection and Self-representation Processes of University Community in Modern Ukraine (on the materials of Kharkiv University) - Рачков, Євген (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The paper investigates the university identity crisis in Ukraine during the modern periodby the example of Kharkiv University. Special attention is given to symbolic manifestations of “challenges” which the university have been faced with during the late 20th – early 21st century. For this purpose, the sign environment of the university is considered as an indicator of the university community identity. We investigate also the way the peculiarities of formation and functioning ofuniversity symbols are correlated to a state of the university corporate consciousness.